Twelve years of iPads and apps in schools: What conditions support effective practices in K-6 classrooms? - Falloon, Garry (Frontiers in Education, 2023)
Since their release in 2010, iPads and their associated apps have been touted as ‘game changers’ for schools struggling with technology provisioning issues, that limited their ability to fully leverage the educational potential of digital devices on a ‘whole class’ basis (Coghlan, 2011). Since then, a variety of schemes have been implemented such as ‘Bring Your Own Device’ (BYOD) and portable ‘device pods’, as systems for improving access to, and utilisation of, mobile technologies in classroom curriculum. In many schools, concurrent to these initiatives have been improvements in technology infrastructure, including upgrades to external connectivity via the advent of high-speed fibre-based broadband, and internally through the establishment of school wifi networks and associated online security systems. Aligned with these developments has been a growing body of research exploring how teachers at all levels of education systems have incorporated these new resources into their curriculum, and examining what, if any, benefits have resulted. This article is an analysis of key findings from four published studies undertaken by the author between 2015 and 2021 in New Zealand K-6 schools, to build understanding of factors that contributed to the effective practices with mobile devices witnessed in the research classrooms. While numerous separate studies have been undertaken exploring specific outcomes from the use of iPads and other mobile technologies in different educational contexts, the analysis presented in this article attempts to identify common factors existing across four purposively selected studies, that contributed to their success. The studies were deliberately chosen to provide a broad overview of applications of this technology in different K-6 classrooms for different purposes, supporting deeper understanding of the factors that underpin effective teaching and learning with and through mobile devices, in schools. This is important, as it builds knowledge of the fundamental foundations to effective educational use of mobile devices, regardless of the learning context in which they are used, and could assist teachers in designing, implementing and assessing curricular that optimises the learning potential of these devices.